2019
DOI: 10.1111/rda.13538
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms of the melatonin receptor 1A gene that affects the reproductive seasonality and litter size in Small Tail Han sheep

Abstract: Previous researches have shown that MTNR1A plays an essential role in sheep reproduction. However, most researches focused more on the reproductive seasonality of sheep, and few scientists had studied the association of polymorphisms of the MTNR1A gene with ovine litter size and reproductive seasonality. Therefore, we chose MTNR1A gene to detect its novel sequence polymorphisms and population genetics and analyse their association with seasonal reproduction and litter size in ewes. The mRNA expression level in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 39 publications
0
23
0
Order By: Relevance
“…However, there are few reports about MTNR1B . In our early study on variation of the genome in 89 sheep, we found a significant single nucleotide polymorphism rs400827589 in the re‐sequencing data (Pan et al., 2018), and several other significant SNPs from which have been published in our early reports (He, Zhang, Liu, & Chu, 2019; Zhou et al., 2018). Therefore, in order to better understand the function of this mutation in MTNR1B , we explored the polymorphic distribution using a large population and then investigated the association with litter size and reproductive seasonality in sheep.…”
Section: Introductionmentioning
confidence: 70%
“…However, there are few reports about MTNR1B . In our early study on variation of the genome in 89 sheep, we found a significant single nucleotide polymorphism rs400827589 in the re‐sequencing data (Pan et al., 2018), and several other significant SNPs from which have been published in our early reports (He, Zhang, Liu, & Chu, 2019; Zhou et al., 2018). Therefore, in order to better understand the function of this mutation in MTNR1B , we explored the polymorphic distribution using a large population and then investigated the association with litter size and reproductive seasonality in sheep.…”
Section: Introductionmentioning
confidence: 70%
“…As the connection between the ovary and the uterus [21], recent researches demonstrated that oviduct is essential in hosts fertilization and preimplantation development of the embryo [22][23][24], however, the in-depth molecular mechanisms have not been elucidated. In the present study, an indigenous Chinese sheep with sheep (Ovis aries) breed with excellent lambing performance (year-round estrous, 2.61 lambs per year on average), STH sheep [25,26] was selected, RNA-Seq was performed on oviduct to investigate the transcriptomic pro les during follicular phase and luteal phase in sheep with two FecB genotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Combined with our previous data on 768 sheep from seven breeds, which was collected via whole-genome resequencing, some SNPs were screened out (Zhang et al, 2019(Zhang et al, , 2020He et al, 2019), including rs421947730 and rs160510212 of FLT3; rs429977514, rs408772397, and rs426897754 of NLRP5; and g.37866222C > T and rs1092900782 of TGIF1. Primers to genotype these SNPs were designed by MassAR-RAY® Assay Design (v.3.1).…”
Section: Design Of the Primer And Synthesizing And Genotyping Of The Locusmentioning
confidence: 99%